Aplicação do formalismo SAN para avaliação de desempenho de uma equipe de desenvolvimento de software baseada no modelo Waterfall - Massitela, Ildo Inês Robão (2016)
The proliferation of the use of software on a daily basis from various institutions is an indisputable fact, whether academic institutions, industrial, commercial, among others. This great looking software creates a great pressure environment in academia and software industry regarding the responsiveness of the great demand. The performance assessment can be a major benefit to the institutions, decision-making can contribute in increasing and improving the responsiveness of growing demand. This paper aims to show, based on a case study, the use of stochastic modeling for performance evaluation of a software development team that has the waterfall model based software design. Despite being a model that has been criticized, it has been a feature in various software projects for its rigid structure and focused management. Some of the factors that ensure a good management are very different design phases where one phase does not start without the other has finished and documentation that helps to focus the institutional history over time.